2019
DOI: 10.1016/j.jcrs.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Edge profile of commercially available square-edged intraocular lenses: Part 2

Abstract: Short running head: Edge profile of square edge intraocular lenses-Part 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Edge design has also been shown to provide an important role in development of PCO and subsequently the risk of Nd:YAG capsulotomy [5] with previous research [22][23][24][25][26][27][28] demonstrating that IOLs with a square-edged optic profile are associated with less PCO than those with a round-edged profile. While all of the IOLs assessed in this study are marketed as having a square-edged profile, it could be the case that the degree of sharpness of the posterior optic edge may have some bearing on the variation in the PCO inhibiting properties displayed by different IOLs [29]. In addition, a study [30] reported that IOLs with a radius of curvature of <10.0 mm appear to have good PCO performance.…”
Section: Discussionmentioning
confidence: 91%
“…Edge design has also been shown to provide an important role in development of PCO and subsequently the risk of Nd:YAG capsulotomy [5] with previous research [22][23][24][25][26][27][28] demonstrating that IOLs with a square-edged optic profile are associated with less PCO than those with a round-edged profile. While all of the IOLs assessed in this study are marketed as having a square-edged profile, it could be the case that the degree of sharpness of the posterior optic edge may have some bearing on the variation in the PCO inhibiting properties displayed by different IOLs [29]. In addition, a study [30] reported that IOLs with a radius of curvature of <10.0 mm appear to have good PCO performance.…”
Section: Discussionmentioning
confidence: 91%
“…Recent research has shown that edges of such IOLs vary but are smoother than designs from 10 years ago. 43 Of 9 hydrophobic acrylic IOLs in one study, Clareon® had the lowest edge thickness at 167.2 microns 43 while another found that the IOL designs with optic edge curvature and full functional optics, such as Clareon®, demonstrated the lowest level of glare-type photic phenomena. 44 The Clareon® IOL features a full 6.0 mm optic and a modified edge profile where the center point of the edge radius lies posterior to the optical plane, designed to reduce dysphototopsia.…”
Section: Discussionmentioning
confidence: 99%
“…20 Nevertheless, the sharpness of the posterior edge varies not only among different materials in the sense that hydrophilic acrylic IOLs generally feature rounder edges because of postprocessing hydration and swelling, but also among IOLs made of similar hydrophobic materials. 25,26 Nanavaty and associates stated that IOLs with a radius of curvature of less than 10.0 mm provide an effective barrier effect. Both IOLs exhibit a sharp edge profile, with the Vivinex XY1 showing an even sharper posterior edge with 7.6 mm radius of curvature and an even thinner edge profiles of 150.5 mm compared to the AcrySof SN60WF (radius of curvature: 8.5 mm; edge thickness: 197.7 mm).…”
Section: Three Years Postoperatively the Vivinex Xy1 Iolsmentioning
confidence: 99%
“…Both IOLs exhibit a sharp edge profile, with the Vivinex XY1 showing an even sharper posterior edge with 7.6 mm radius of curvature and an even thinner edge profiles of 150.5 mm compared to the AcrySof SN60WF (radius of curvature: 8.5 mm; edge thickness: 197.7 mm). 25 A common feature of the Vivinex XY1 and the AcrySof SN60WF IOL is that the optic edge does not exhibit a stepped (''enhanced'') square edge design. In this area the impeded fusion of the capsule leaves results in a lack of bending of the posterior capsule around the posterior optic edge.…”
Section: Three Years Postoperatively the Vivinex Xy1 Iolsmentioning
confidence: 99%